Monte Carlo Methods to Simulate the Propagation of the Created Atomic/ Nuclear Particles from Underground Piezoelectric Rocks through the Fractures Before the Earthquakes - Bahari, A.; Mohammadi, S.; Shakib, N. S.; Benam, M. R.; Sajjadi, Z. (National Research and Innovation Agency, 2024)
Until now, many studies have been performed on particle radiations before or during earthquakes (EQs). Neutron, gamma, electron, proton, and ultra-low frequency (ULF) photons are among the particles, detected during EQs. In our previous study, with the help of piezoelectricity relationships and the elastic energy formula, the Monte Carlo N‐Particle eXtended (MCNPX) simulation code was applied to find the amount of created atomic/nuclear particles, the dominant interactions; and the energy of the particles for various sizes of quartz and granite blocks. In this study, using the MCNPX simulation code, we have estimated the flux of the particles (created from under-stressed granitic rocks) at different distances from the EQ hypocenter inside the fractures, filled with air, water, and CO2. It was found that inside a water-filled fracture, the particles do not show the flux far from the EQ hypocenter. However, inside the gases like air and CO2 with the normal condition density, different types of particles can have a flux far from the source (more than a kilometer) and they might reach themselves to the surface in the case that the EQ hypocenter is very shallow (0-5 km). However, for deep EQs, it seems that the most detected nuclear particles on the surface should pass via the vacuum-filled fractures and reach the surface. Moreover, it was concluded that the higher the density of the fracture’s filling fluid, the less distance that the particles can have a flux.